2004
DOI: 10.1080/09537100310001643999
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-released supernatants increase migration and proliferation, and decrease osteogenic differentiation of bone marrow-derived mesenchymal progenitor cells underin vitroconditions

Abstract: Platelet-rich plasma is currently promoted to serve as an adjuvant for bone grafts to enhance quantity and quality of newly forming bone; however, the underlying cellular mechanisms are not fully understood. We show here that supernatants of leukocyte-depleted thrombin-activated platelets increase migration and proliferation, and decrease osteogenic differentiation of bone marrow-derived mesenchymal progenitor cells under in vitro conditions. Using neutralizing antibodies raised against platelet-derived growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
142
5
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(169 citation statements)
references
References 36 publications
18
142
5
3
Order By: Relevance
“…Platelet-derived growth factor (PDGF) is a potent MSC mitogen that plays an important role in OB proliferation and differentiation, with the addition of PDGF to osteogenic MSC cultures strongly inhibiting OB differentiation and function in vitro. (11)(12)(13)(14) Two signaling pathways that are strongly activated in response to PDGF are the class I phosphatidylinositol-3-kinase/Akt (PI3K) and mammalian target of rapamycin (mTOR) pathways. (15,16) Class I PI3Ks are heterodimeric complexes composed of a catalytic p110 subunit (a, b, d, g) and a regulatory p85, p55, p50, or p101 subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-derived growth factor (PDGF) is a potent MSC mitogen that plays an important role in OB proliferation and differentiation, with the addition of PDGF to osteogenic MSC cultures strongly inhibiting OB differentiation and function in vitro. (11)(12)(13)(14) Two signaling pathways that are strongly activated in response to PDGF are the class I phosphatidylinositol-3-kinase/Akt (PI3K) and mammalian target of rapamycin (mTOR) pathways. (15,16) Class I PI3Ks are heterodimeric complexes composed of a catalytic p110 subunit (a, b, d, g) and a regulatory p85, p55, p50, or p101 subunit.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among these cells are mesenchymal progenitors that can be attracted by signaling molecules released from activated platelets. 8,9 The functional role of platelets during the early stages of bone regeneration is not, however, entirely clear. Platelets may support the immigration of mesenchymal progenitors by increasing their capacity to digest the fibrin-rich matrix.…”
mentioning
confidence: 99%
“…In vitro studies showed that PRP activates proliferation and migration of osteoprogenitor cells (Gruber et al, 2003(Gruber et al, , 2004 but decreases osteogenic differentiation of BMSC (Gruber et al, 2004). This suggests that the osteogenic effect of PRP mainly relies on proliferation and migration, rather than on induction of differentiation.…”
Section: The Underlying Effect Of Platelet-derived Products: Knowledgmentioning
confidence: 99%